CORRELATION OF THE PREVALENCE PHYSICAL FUNCTION ABILITY WITH AGE AND PHYSICAL INACTIVITY IN ELDERLY PEOPLE - Maulida, Shidqi
Capacity for physical function and skeletal muscles in elderly will decrease with age, decreasing by 1% every year and at least 3% if you are 70 years or older. Each individual has a different level of decline. Age, gender, physical inactivity, and history of chronic disease are factors that interact to reduce the capacity (mass and strength) of skeletal muscles. Objective: To explore the prevalence of physical function ability and how closely it is related to age and physical inactivity in the elderly. Method: Observational study with a quantitative descriptive correlation analysis, 46 elderly people were included in the research subject inclusion criteria. Measurements and normative values for physical function ability using the Asian Working Group of Sarcopenia (AWGS) standards, physical inactivity measurements use the ActivPAL accelerometer with a usage time of 24 hours for 4 days used on the front of the thigh. Results: Non-Sarcopenia 19%, Pre-sarcopenia 22%, Sarcopenia 37%, and Severe Sarcopenia 22%. Male 65% and Female 59%. The relationship between physical function ability and age is 0.374 in the weak category and physical inactivity -0.731 in the strong category. The degree of relationship between age and muscle strength (MS) -0.192 and Appendicular Skeletal Muscle mass Index (ASMI) -0.189 is in the weak category, while physical performance (PF) -0.482 is in the moderate category. In the physical inactivity variable with MS (–0.593) and PF (-0.451) in the moderate category, ASMI (- 0.613) in the strong category. Conclusion: as many as 59% of elderly people have experienced sarcopenia, and it is dominated by men. Age-related decline in physical function abilities cannot be prevented, but the decline can be slowed by limiting physical inactivity behaviour and replacing it with more active physically.